Die Rolle von Anschauung und Begriff bei Johann Gottlieb Fichte Mit Kant über Kant hinaus - de Rosales Chacón, Jacinto Rivera (Begriff und Konkretion (BK), 2021)
»The Role of Intuition and Notion in Johann Gottlieb Fichte. Looking Beyond Kant With Kant«: There was probably no other thinker whom Johann Gottlieb Fichte felt as connected to as Immanuel Kant. Fichte studied Kant's critical oeuvre and his newly defined roles of intuition and notion in epistemology intensely. That also inspired impulses through which he reoriented himself methodically to grow even beyond Kant. Despite the differences, Fichte's Wissenschaftslehre is located to an astonishing extent within the horizon of Kant's theory.